Mobile banking in Bangladesh: An opportunity with constraints? - Bloem, Jeffrey R.; Rahman, Khandker Wahedur (Brac Institute of Governance & Development, 2023)
Digital financial services (DFS), particularly mobile banking, have the potential to extend financial services to unbanked populations.[1] Specifically, DFS reduce direct and indirect transaction costs. Mobile banking allows clients to access bank accounts, save money, and send and receive payments directly from their mobile phones, eliminating travel to a physical bank. Additionally, mobile banking reduces social or administrative constraints—such as in-person meetings and paperwork, and safety concerns while travelling with money—which can be especially salient for women.